Pemberdayaan Masyarakat melalui Pelatihan Pembuatan Kroket Pisang sebagai Produk Kreatif UMKM di Desa Blang Baro, Aceh Jaya - Putra Ari Pujangga; Rahmat Oriza; Yofi Amalia; Julia Ramadhani; Aja Cut Maulinda; Jelita Navasta; Eka Riani; Niva Ramadhani (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to empower the people of Blang Baro Village, Teunom District, Aceh Jaya Regency, through training in the production of banana croquettes as a creative MSME product. This activity was motivated by the limited diversification of MSME products and the low added value of local commodities, particularly bananas. The community service method uses a participatory approach that actively involves the community from planning to evaluation, including socialization, production training, packaging assistance, and introduction to marketing strategies. The concrete outputs of this program include: 1) ready-to-sell banana croquettes with hygiene standards; 2) attractive packaging design; 3) the formation of a new MSME group consisting of 20 women from the Family Welfare Movement (PKK); and 4) a 40% increase in participants' knowledge scores based on pre- and post-tests. The results of the activity indicate an increase in participants' skills in processing bananas into marketable products and an increase in entrepreneurial motivation. This program contributes to strengthening the village's creative economy and provides an alternative source of income for the community.